1996
DOI: 10.1364/ao.35.005340
|View full text |Cite
|
Sign up to set email alerts
|

Optical fiber magnetic field sensors with ceramic magnetostrictive jackets

Abstract: Optical fibers coated by magnetostrictive ceramic films were tested with a Mach-Zehnder interferometer in an open-loop mode. The sensors exhibited excellent linearity and good sensitivity. The response of ceramic-jacketed fibers was not affected by small dc fluctuations that are due to the linear behavior of tested ceramic coatings in low magnetic fields. Tested ceramic materials included magnetite, γ-Fe(2) O(3), nickel ferrite, and cobalt-doped nickel ferrite (NCF2) jackets. The latter showed the best perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…For that an optical fiber is bonded to a sample, or by thin-film deposition with a magnetostrictive material. The most commonly used magnetostrictive sensing elements were optical fibers coated with nickel [43], metallic glasses such as Metglass 2605S2 or Vitrovac 40-60 [44][45][46][47] [48,49].…”
Section: Magnetic Force Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For that an optical fiber is bonded to a sample, or by thin-film deposition with a magnetostrictive material. The most commonly used magnetostrictive sensing elements were optical fibers coated with nickel [43], metallic glasses such as Metglass 2605S2 or Vitrovac 40-60 [44][45][46][47] [48,49].…”
Section: Magnetic Force Sensorsmentioning
confidence: 99%
“…Optical fibers coated with magnetostrictive ceramic films were tested by Sedlar et al [49], by using a modified Mach-Zehnder interferometer operating in an open-loop configuration. The sensors exhibited excellent linearity and good sensitivity.…”
Section: −7mentioning
confidence: 99%
“…Few reports exist there in the literature describing the possible use of magnetostrictive transducers in fibre optic based sensors [19][20][21]. Sedlar et al [19] reported the magnetic field sensing properties of ferrite coated single mode optical fibres.…”
Section: Introductionmentioning
confidence: 99%
“…Sedlar et al [19] reported the magnetic field sensing properties of ferrite coated single mode optical fibres. Rengarajan and Walser [20] reported the fabrication of a high speed fibre optic sensor for magnetic field mapping.…”
Section: Introductionmentioning
confidence: 99%
“…All-optical switches and attenuators enable routing of data without the need for optical to electrical conversion. Optical fiber based devices have also been widely used for optical amplitude modulator (Fang and Taylor 1994;Lee et al 1997;Matias et al 2001) and imaging (Boppart et al 1997;Nelson et al 1997;Sedlar et al 2000;Popovic et al 1996;Keplinger et al 2003). Variable fiber-optic-based devices have been developed with piezoelectric (Herding et al 2004), electrostatic (Hoffmann et al 1999;Cochran et al 2004), thermal (Nagaoka 1999;Bernstein et al 2004;Comtois et al 1997), and electromagnetic (Deeter 1995;Tearney et al 1996;Dhaubanjar 2006;Sendoh et al 2003) actuations.…”
Section: Introductionmentioning
confidence: 99%